Penerapan Kriptografi RSA Dalam Mengamankan File Teks Berbasis PHP - Dicky Apdilah; Heru Swanda ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - Along with the development of communication technology human needs in the use of technology are increasing, especially in data storage. One way to improve security for data is by using cryptographic methods. RSA Algorithm (Rivest Shamir Adleman) is one method in the branch of cryptography, where RSA is a type of asymmetric cryptography that uses 2 keys, namely public and private keys. The problem of increasing the security of the public key and private key in RSA (Rivest Shamir Adlema) is that the Linear Congruential Generator (LCG) method is needed, LCG is used to generate a set of random numbers to n, where a set of random numbers will be taken that have a number value prime. One method for generating prime numbers is The Sieve Of Eratosthenes algorithm, The Sieve Of Eratosthenes algorithm is a classic algorithm for determining all prime numbers until the n-number is specified. The way the The Sieve Of Eratosthenes method works is to eliminate numbers that are not prime numbers, resulting in a collection of prime numbers. The prime number generated by the The Sieve Of Eratosthenes algorithm will be used for the public key and private key in the RSA criterion. Keywords - RSA, LCG, The Sieve of Eratosthenes.